Endoscopic Microvascular Decompression for Hemifacial Spasm: The Benefits of the Angled Endoscope and Intraoperative Neuromonitoring. (16th November 2020) - Blue, Rachel; Howard, Susanna; Spadola, Michael; Kvint, Svetlana; Lee, John Y.K
Abstract: INTRODUCTION: Hemifacial spasm (HFS) is a condition of spasmodic contractions secondary to compression of the facial nerve. Microvascular decompression (MVD) was initially performed with the microscope but visualization is restricted to a direct line of site necessitating a larger craniotomy and increased retraction. The endoscope provides enhanced visualization and the ability to see around corners. Another technical advance is intraoperative neuromonitoring. Specifically, the lateral spread response (LSR) assesses the efficacy of decompression. METHODS: A case report of a patient undergoing endoscopic MVD for HFS. RESULTS: A 57-year-old with HFS underwent endoscopic MVD of the facial nerve. Baseline neuromonitoring of the zygomatic branch of the facial nerve was activated at 1.2mA. LSR was seen of the buccal and mandibular branches at 2.2mA. A straight endoscope was used for the initial approach, CSF drained and arachnoid dissected for visualization of the facial nerve. Neurovascular compression was not identified. A 30-degree endoscope was directed medially and inferiorly and compression at the root entry zone (REZ) was identified and decompressed. Following decompression, LSR to the buccal nerve was present at 3.2mA, and LSR to the mandibular branch at 3.6 mA. While this was an improvement, significant LSR was still present. As such, the angled endoscope was directed laterally and a second area of compression identified at distal portion of the nerve and decompressed. Following decompression, the LSR of the buccal and mandibular branches were not activated until 9.8mA, indicating good decompression. The patient tolerated the procedure well and had complete resolution of her symptoms. CONCLUSION: The 30-degree endoscope visualized pathology that could not be seen at 0-degrees. Additionally, the use of LSR guided the surgeon to an additional area of pathology. Interestingly, the second decompression had a greater response based on LSR, which is contradictory to the belief that the pathophysiologic compression occurs at the REZ. This case demonstrates the benefit of the endoscopic technique and LSR as well as the need to look for compression not only at the root entry zone, but also at the distal portion of the nerve.